Determination of Sugar Content in Commercial Fruit Juices by Refractometric, Volumetric and Chromatographic Methods - Buiarelli, Francesca; Filippo, Patrizia Di; Pomata, Donatella; Riccardi, Carmela; Rago, Daniela (Journal of Nutritional Therapeutics, 2016)
In this paper several approaches are discussed for the direct analysis of the main sugars in different fruit juices. Refractometry, thin layer chromatography, volumetric analysis and high performance liquid chromatography with refractive index detector were tested and the results compared, discussing the advantages and disadvantages of each of them. Whereas the first method gives generically indications on the whole content of sugar and it doesn’t require any prior manipulation of the sample, thin layer chromatography is useful only for qualitative purpose, on the other hand the third method, after removal of interferences, makes possible the determination of the reducing and not reducing sugar, and the last one allows the qualitative and quantitative determination of the saccharides singularly. It’s very important to have not only knowledge about the chemical analysis of carbohydrates and their physicochemical properties, but especially how the methods can be used in product development for benefit of the public.